Analisis Faktor Yang Berhubungan Dengan Pemilihan Tempat Persalinan Di Wilayah Kerja Puskesmas Kairatu Barat - Anggriani La amin, Runi; Rocmaeda, Siti (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2025)
Giving birth in a health facility is the right choice because it can provide Basic Emergency Obstetric and Neonatal Services (PONED) so that a referral can be made immediately if necessary, whereas if you give birth at home and require medical treatment it cannot be treated immediately. Methods: This research is an analytic descriptive study with a retrospective approach. The population is mothers who gave birth in the January-April 2023 range, with a sample size of 70 respondents. The sampling technique uses total sampling with the chi-square analysis test used. Results: Statistical tests using Chi-Square showed that the ? value was 0.330 where > ? (0.05) so it could be concluded that statistically there was no significant relationship between parity and choice of place of delivery, the ANC visit variable was found to be ? value 0.254 where > ? (0.05) and it can be concluded that statistically there is no significant relationship between ANC visits and the choice of place of delivery and there is a relationship between the distance from home to a health facility and the choice of place of delivery in the work area of the West Kairatu Health Center with a ? value of 0.032 where < ? (0.05) . Conclusion: There is no relationship between parity, ANC visits and the choice of birth place and there is a relationship between the distance from home to a health facility and the choice of birth place in the West Kairatu Health Center working area